2007
DOI: 10.1175/jas3917.1
|View full text |Cite
|
Sign up to set email alerts
|

Monsoon Dynamics with Interactive Forcing. Part II: Impact of Eddies and Asymmetric Geometries

Abstract: The roles of eddies and forcing asymmetry in the dynamics of the large-scale monsoon circulation are investigated with a general circulation model. The net impact of eddies is found to be a slight weakening of the zonal mean monsoon circulation. The eddies strongly impact the momentum budget of the circulation, but the qualitative behavior of the monsoon flow is not substantially altered. The introduction of asymmetric forcing reveals the limitations of axisymmetric studies in representing the fully three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 19 publications
(18 reference statements)
9
75
0
Order By: Relevance
“…Held and Hou, 1980). In idealized models of monsoons, Privé and Plumb (2007b) found that zonal asymmetries introduced numerous complexities to such axisymmetric theories, but that the position of the s b peak still served to delineate the poleward boundary of the monsoon circulation, with maximum ascent and precipitation occurring just equatorward of this peak (also Privé and Plumb, 2007a). This is consistent with the treatment of zonal asymmetries introduced by Emanuel (1995) in his theory of moist, thermally direct flow that conserves absolute angular momentum in the free-troposphere.…”
Section: Assessment In a Quasi-equilibrium Frameworksupporting
confidence: 62%
See 1 more Smart Citation
“…Held and Hou, 1980). In idealized models of monsoons, Privé and Plumb (2007b) found that zonal asymmetries introduced numerous complexities to such axisymmetric theories, but that the position of the s b peak still served to delineate the poleward boundary of the monsoon circulation, with maximum ascent and precipitation occurring just equatorward of this peak (also Privé and Plumb, 2007a). This is consistent with the treatment of zonal asymmetries introduced by Emanuel (1995) in his theory of moist, thermally direct flow that conserves absolute angular momentum in the free-troposphere.…”
Section: Assessment In a Quasi-equilibrium Frameworksupporting
confidence: 62%
“…Orography may help to organize the flow, confining the pool of high-entropy air and even 332 W. R. BOOS AND K. A. EMANUEL insulating it from the colder midlatitudes (Chou et al, 2001;Privé and Plumb, 2007b). The degree to which this high-entropy pool is altered by the land surface thermal forcing, horizontal entropy advection in the subcloud layer, and moisture radiation feedbacks deserves further exploration in separate work.…”
Section: Wind-evaporation Feedbackmentioning
confidence: 99%
“…The high terrains of the plateau not only affect the South Asian monsoon by preventing cold and dry extra-tropical atmosphere from convecting with warm and moist tropical air masses (Chou et al, 2001;Privé and Plumb, 2007;Boos and Emanuel, 2009), but also play an unnegligible role in influencing the East Asian monsoon by altering eastward westerly jet (Liang and Wang, 1998;Xie et al, 2006;Wu et al, 2007). Shaped by local topography, water vapour sources supplying to the plateau is divided into three routes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A view, which has been prevailing since the classical studies by Yeh et al (1957) and Flohn (1957), interprets the Tibetan Plateau as an elevated heat source driving the Asian monsoon, with sensible and latent heat fluxes dominating over the eastern and western Plateau, respectively (Luo and Yanai 1984;Webster et al 1998;Wu and Zhang 1998;Yanai and Wu 2006). An alternative hypothesis has, however, been emerging in recent years, by which the Tibetan Plateau prevents dry and cold extratropical air from ''ventilating'' the moist and warm tropics and subtropics (Chou et al 2001;Prive and Plumb 2007). Indeed, in a recent modeling study, BK10 showed that the main circulation and thermodynamical features of the South Asian monsoon were largely unaffected in GCM experiments in which the Tibet was removed but a narrow Himalaya was retained.…”
Section: Introductionmentioning
confidence: 99%